Quality of life and factors associated among public university employees retired due to disabilities - Aline Aparecida Oliveira Moreira; Júlia Trevisan Martins; Maria Lucia do Carmo Cruz Robazzi; Maria José Quina Galdino; Renata Perfeito Ribeiro; Maynara Fernanda Carvalho Barreto (Universidade de São Paulo, 2023)
Abstract Objective: to analyze quality of life and factors associated among public university employees retired due to disabilities. Method: a cross-sectional study conducted with a sample of public university employees retired due to disabilities. A characterization questionnaire and the World Health Organization Quality of Life - Disabilities instrument were applied via telephone or online contacts from November 2019 to September 2020. The associated factors were verified through multiple linear regression. Results: of the 80 retirees due to disability, 15% were professors and 85% had a technical-administrative career. As for the factors associated with Quality of Life, continuous medication use (βadj: -0.25; p=0.02) and problems in the nervous system (βadj: -0.21; p<0.05) were associated with the Overall domain; continuous medication use (βadj: -0.23; p=0.04), to the Physical domain; smoking (βadj: -0.21; p<0.05) and mental and behavioral disorders (βadj: -0.21; p<0.01), to the Psychological domain; smoking (βadj: -0.46; p<0.01) and respiratory (βadj: -0.21; p=0.03) and circulatory (βadj: -0.21; p=0.03) problems, to the Social domain; smoking (βadj: -0.33; p<0.01) and problems in the nervous system (βadj: -0.22; p=0.04), to the Environmental domain; mental and behavioral disorders, to the Disabilities module (βadj: -0.29; p<0.01) and to the Discrimination domain (βadj: -0.21; p<0.05); and smoking (βadj: -0.32; p<0.01) and problems in the nervous system (βadj: -0.20; p<0.05), to the Inclusion domain. The Autonomy domain did not present any association. Conclusion: the retirees under study presented impaired Quality of Life.